Value-Based Concepts of the Art of Oratory - Malikova, A.M.; Bolyssova, K.M.; Rakimzhanova, S.K. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The relevance of the scientific article is that we, having separated from the “Soviet and post-Soviet” environment, are in search of ourselves, trying to fill the space of the yesterday's axiological cognition with the values of new content, seeking to find our place in the Western and Eastern realms. Indeed, the teachings of Hodja Ahmet Yassawi, who occupies a great place in our spiritual world, are very relevant now. His words “Know thyself first” seem to be very significant. Then there are Kazakh biys and orators — spiritual mentors of the society, erecting barriers to the decline of the moral space of society. And if so, Kazakh oratory is one of the majestic spiritual universes that formed the system of values. The heritage left by them to descendants is priceless, and centuries-old history is a witness to it. Spiritual culture originates in the samples of folk wisdom and advanced teachings. People define their relationships, principles of communication and other types of contact primarily on the basis of folk wisdom. Thus, in this article we will consider the problem of common human values, which are in close interrelation with each other, in two hypostases. First, we will analyze the characteristics that are given in oratory to a person (negative-positive) from the perspective of human attitudes and traits. Secondly, we aim to take a deeper look into the spiritual and axiological consciousness, into its inner aspects and mysteries.
Шешендік өнердің құндылыққа негізделген концепциялары
Ценностные концепции ораторского искусства
Keywords: oratory; value, knowledge system; tradition; folk wisdom; worldview; spiritual essence; axiological consciousness; nation; communication